Congenital Intranasal Glioma - Sajad Ahmad Salati; Ajaz Ahmad Rather (Case Reports in Surgery)
Congenital midline swellings of nose are encountered rarely, and nasal gliomas constitute about 5% of such lesions. Various theories have been suggested to explain the pathogenesis. Imaging preferably by MRI is mandated to study the extent and to rule out intracranial extension. Treatment is complete excision, and the approach depends upon the extent of the lesion and availability of expertise. We present the management of one such case of congenital intranasal glioma without any intracranial extension that presented as a septal polyp.